2017
DOI: 10.1037/bdb0000040
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of caregiver training via telecommunication for rural Icelandic children with autism.

Abstract: This article describes the development and results of behavioral training via telecommunication for three caregivers of children with autism. A single-subject, multiple baseline experimental design, replicated across caregivers, preschool children with autism, and tasks, was used to evaluate the effects of the training. Dependent measures were collected in vivo and via telecommunication and included parent, teacher, and child responses during naturalistic play. The intervention involved teaching caregivers met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(60 citation statements)
references
References 36 publications
2
58
0
Order By: Relevance
“…Translated Materials. Seven studies (Alnemary et al, 2015;Dai et al, 2018;Guðmundsdóttir et al, 2017;Guðmundsdóttir et al, 2018;Lee, 2015;Neely et al, 2020;Tsami et al, 2019) reported using translated materials either during the baseline phase or the training phase of the study. These studies used different methods for the translation process.…”
Section: Changes In Structure and Process Of Service Deliverymentioning
confidence: 99%
“…Translated Materials. Seven studies (Alnemary et al, 2015;Dai et al, 2018;Guðmundsdóttir et al, 2017;Guðmundsdóttir et al, 2018;Lee, 2015;Neely et al, 2020;Tsami et al, 2019) reported using translated materials either during the baseline phase or the training phase of the study. These studies used different methods for the translation process.…”
Section: Changes In Structure and Process Of Service Deliverymentioning
confidence: 99%
“…Another significant trend we observed was the extensive reach of telehealth, with many studies actively recruiting children who resided in rural regions and through intercontinental training of interventionists and families. Multiple studies recruited and included families who resided in rural areas [ 19 •, 20 •, 21 •, 22 •, 37 •]. For example, RUBI ASD Network Parent Training was delivered through synchronous video-conferencing between a clinic and a satellite site clinic [ 22 •].…”
Section: Introductionmentioning
confidence: 99%
“…Barkaia et al demonstrated successful intercontinental coaching to early intervention providers in Eastern European countries, resulting in improvements in intervention provider implementation and increases in children’s requests and vocal imitation [ 38 •]. Guðmundsdóttir et al demonstrated effective training on a naturalistic intervention sequence over synchronous telehealth to families and a special education teacher in a rural Icelandic location [ 37 •]. Tsami et al examined the acceptability and feasibility of FCT with 18 parent-child dyads from multiple countries, recruiting children with parents who did not speak or understand English [ 28 •].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar study, Guðmundsdóttir, Sigurðardóttir, and Ala'i‐Rosales () used telehealth to train a caregiver to promote the language of a child with autism in rural Iceland. The experimenter also occasionally conducted some in‐situ training sessions.…”
mentioning
confidence: 99%